The Accuration of Progesterone Test Kits for Early Pregnancy Diagnosis in Ettawa Cross Goat - Juli Melia; Desriwan Angga Putra; Syafruddin Syafruddin; Tongku Nizwan Siregar; Teuku Reza Ferasyi; Wahyu Eka Sari (The Faculty of Veterinary Medicine of Syiah Kuala University, 2023)
This research aimed to determine the accuracy of the progesterone test kit for milk and blood as means of early pregnancy diagnosis in Ettawa cross goats (PE). Five lactating PE goats were used in this study and were synchronized with PGF2α intramuscularly. The result is that all goats showed a sigh of estrus. Four goats were mated naturally, while one other was not mated. The determination of day-0 was when the females were standing heat. Early pregnancy diagnosis using dairy cow test strips performed 18-22 days after mating or post-estrus. The accuracy of the diagnosis was confirmed by ultrasound examination on day 35 after mating/post estrus. Diagnosis using the milk progesterone kit showed negative results for five days of examination in all goats, whereas using the blood progesterone kit showed positive results in four goats. When confirmed, using ultrasound showed one goat was diagnosed as not pregnant, and four other goats were diagnosed pregnant. It can be concluded that the use of progesterone dairy cow pregnancy test strip kits is effectively used to diagnose early pregnancy in PE goats with high accuracy in blood samples (100%) and low accuracy in milk samples (20%).